A regression-based model of MSME strategy effectiveness during and beyond the COVID-19 crisis - Trenggonowati, Dyah Lintang; Katili, Putiri Bhuana; Singgih, Moses Laksono; Ridwan, Asep (Journal Industrial Servicess, 2025)
The COVID-19 pandemic has triggered a profound global economic crisis, disproportionately affecting Micro, Small, and Medium-Sized Enterprises (MSMEs) in developing countries such as Indonesia. Unlike previous economic shocks—such as the 1998 Asian Financial Crisis and the 2008 Global Recession—where MSMEs served as economic buffers, the pandemic exposed structural vulnerabilities in digital readiness, innovation capacity, and operational resilience. This study aims to empirically model the effectiveness of MSMEs’ strategic responses during crisis conditions using a multiple linear regression framework. Data were collected from 300 MSMEs across Indonesia through structured questionnaires, followed by classical assumption testing and regression analysis. The model includes six strategic variables: production activities, innovation, rebate strategies, business planning, e-commerce utilization, and product reliability. The results indicate that innovation, e-commerce, and product reliability significantly contribute to MSME effectiveness during disruption. The adjusted  value of 0.147 suggests moderate explanatory power, with potential for future research to examine broader environmental and policy-related variables. This study extends the existing literature by quantitatively identifying key strategic factors that foster MSME resilience—offering not only pandemic-era insights but also long-term guidance for post-crisis adaptation and preparedness. The findings provide a foundation for evidence-based policymaking aimed at enhancing MSME agility, sustainability, and crisis resistance in both current and future contexts.